Mechanical powered portable charger for disaster recovery: design and implementation using hand cranking DC motor and arduino microcontroller - Suhaimi, Nur Hanis Sabrina; Gunawan, Teddy Surya; Kartiwi, Mira (LAP Lambert Academic Publishing, 2013)
This book presents the development of mechanical powered portable charger to charge mobile phone during disaster recovery. It emphasizes on efficient mechanical energy harvesting circuit for charging mobile phone battery with the utilization of intermediate battery. In this book, Sealed Lead-Acid (SLA) or dry battery was selected as an intermediate battery to protect the Lithium Ion battery which is very sensitive to overcharging and discharging. Three modules are employed in this book, including a DC/DC boost converter circuit, SLA charging circuit and mobile phone charging circuit utilizing Arduino microcontroller. During disaster, main power supply will be interrupted. If only the victims can communicate through their mobile phone, there will be high chance that they can be rescued by the rescue team. Note that, the portable cell tower can be set up by the relevant authorities during disaster. This book can benefit government, NGO, or volunteers during disaster, as well as many people in disaster prone area.